1993
DOI: 10.1901/jeab.1993.60-255
|View full text |Cite
|
Sign up to set email alerts
|

Tests of Behavior Momentum in Simple and Multiple Schedules With Rats and Pigeons

Abstract: Four experiments examined the relationship between rate of reinforcement and resistance to change in rats' and pigeons' responses under simple and multiple schedules of reinforcement. In Experiment 1, 28 rats responded under either simple fixed-ratio, variable-ratio, fixed-interval, or variable-interval schedules; in Experiment 2, 3 pigeons responded under simple fixed-ratio schedules. Under each schedule, rate of reinforcement varied across four successive conditions. In Experiment 3, 14 rats responded under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
95
2
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 33 publications
14
95
2
7
Order By: Relevance
“…When VI schedules with different reinforcement rates are arranged in multiple schedules, the typical result is that the component with the richer reinforcement rate is more resistant to change (Nevin et aI., 1983). Analogous results were obtained with FI schedules by Cohen et al (1993). Thus, we expected that responding during peak trials for the FI 10-sec schedule would change less, relative to baseline, than peak-trial responding for the FI 30-sec schedule.…”
Section: Methodssupporting
confidence: 55%
“…When VI schedules with different reinforcement rates are arranged in multiple schedules, the typical result is that the component with the richer reinforcement rate is more resistant to change (Nevin et aI., 1983). Analogous results were obtained with FI schedules by Cohen et al (1993). Thus, we expected that responding during peak trials for the FI 10-sec schedule would change less, relative to baseline, than peak-trial responding for the FI 30-sec schedule.…”
Section: Methodssupporting
confidence: 55%
“…For example, Cohen (1986) demonstrated that drugs such as damphetamine sulfate, haloperidol, sodium pentobarbital, and CCK8 do not operate as other response disrupters (e.g., extinction and food satiation) in showing differences in resistance to change across situations correlated with different rates of reinforcement. In addition, Cohen et al (1993) did not find a relationship between resistance to change and reinforcement density when the reinforcement rates were varied between blocks of training sessions, but they did find a relationship when different rates of reinforcement were correlated with different discriminative stimuli and alternated within sessions (a multiple schedule).…”
mentioning
confidence: 79%
“…They found that if a force (e.g., extinction or satiation) is applied across situations involving high versus low reinforcement rate, resistance to change (behavioral mass) is greater in the situation correlated with the higher rate of reinforcement. Cohen (1986) and Cohen, Riley, and Weigle (1993) used rats as subjects in their momentum studies and also observed that resistance to change was greater in the situation associated with the higher density of reinforcement. These authors also defined particular boundaries to the behavioral momentum effect.…”
mentioning
confidence: 99%
“…The experimental procedures employed with rats in Experiment 3 closely approximate those of Nevin et al (1983) with pigeons and are similar to those used with rats by Cohen, Riley, and Weigle (1993), with the exception that the latter study involved fixed-interval (FI) and intermittent FR schedules. We held rate of reinforcement constant in both components of the multiple schedule (i.e., VI 60 s VI 60 s) and varied only the type of liquid reinforcer in each component (i.e., sucrose or citric acid solution).…”
Section: Discussionmentioning
confidence: 99%